1965
DOI: 10.1002/pssb.2220100229
|View full text |Cite
|
Sign up to set email alerts
|

Ein Modell für die Keimbildung der Stapelfehlertetraeder in abgeschrecktem Gold Von

Abstract: Die Keimbildung von Stapelfehlertetraedern in abgeschrecktem Gold wird auf Grund eines Modells erkliirt, wonach die Keime durch einen DreierstoO von Einfach-, Doppel-und Dreifachleerstellen gebildet werden. Die Keime wirken nach ihrer Bildung als effektive Senken fur die beweglichen Leerstellen. Es werden Gleichungen fur die Variation der Tetraederdichte mit Leerstellenkonzentration und Temperatur und fur die Kinetik der Keimbildung gegeben. Ein quantitativer Vergleich zwischen Theorie und Experiment ergibt it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

1965
1965
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
1
3
0
2
Order By: Relevance
“…Thus, to summarize, we now have direct evidence that a vacancy type defect undergoes long range migration in gold at temperatures as low as 250 K. At temperatures up to 333K the vacancies aggregate to form SFT directly in agreement with the models of de Jong and Koehler (1963) and Chik (1965) and although we do not have direct evidence regarding the form of the nucleus the concept of a minimum critical nucleus size appears to be valid. Above 333 K it has been shown that there is a decrease in both nucleation rate and C, and this is consistent with two processes occurring simultaneously:…”
Section: -$[110] + 31211supporting
confidence: 69%
See 2 more Smart Citations
“…Thus, to summarize, we now have direct evidence that a vacancy type defect undergoes long range migration in gold at temperatures as low as 250 K. At temperatures up to 333K the vacancies aggregate to form SFT directly in agreement with the models of de Jong and Koehler (1963) and Chik (1965) and although we do not have direct evidence regarding the form of the nucleus the concept of a minimum critical nucleus size appears to be valid. Above 333 K it has been shown that there is a decrease in both nucleation rate and C, and this is consistent with two processes occurring simultaneously:…”
Section: -$[110] + 31211supporting
confidence: 69%
“…Eventually the stair rod dislocations meet to form the apex of the tetrahedron (figure l(c)). An alternative mechanism for SFT formation has been proposed by de Jong and Koehler (1963) and Chik (1965) in which they are nucleated directly by the formation of a hexavacancy from mobile vacancy complexes, that is mono, di and trivacancies.…”
Section: -$[110] + 31211mentioning
confidence: 99%
See 1 more Smart Citation
“…P 2 , l = p: (8) ist 6) Im folgenden wird die durch die Theorie [23] und die experimentellen Ergebnisse von [7] gestutzte Annahme gemacht, daD L, wesentlich stabiler als L, ist.…”
Section: N Allen Proben Wurden Neben Tetraedern Auch Versetzungspolunclassified
“…Diese Unt,ersuchungen bereiten den Weg zum Aufbau eines Modells fur die Keimbildung von Tetraedern, das in der folgenden Arbeit [7] entwickelt wird.…”
Section: Introductionunclassified